Adsorption of Cu(II), Zn(II), Cd(II), Hg(II) and Pb(II) from aqueous solutions on a 2-mercaptobenzimidazole-modified silica gel - Moreira, José C. [UNESP]; Pavan, Luiz C. [UNESP]; Gushikem, Yoshitaka (Springer Nature, 1990)
The chemically modified silica, obtained by reacting 2-mercaptobenz-imidazole with 3-chloropropyl silica gel, was used to adsorb Cu(II), Zn(II), Cd(II) and Pb(II) from aqueous solutions at various pH. Between pH 3-5, the order of selectivity was Hg(II) > Cd(II) ≫ Cu(II) ∼ Zn(II) ∼ Pb(II). Under batch conditions retentions of 100% were achieved for all metals except for Pb(II) where 93% was attained. Under column conditions recoveries of 100% were obtained for all metals. © 1990 Springer-Verlag.
Keywords: 2-mercaptobenzimidazole; cadmium; copper; mercury and lead determination; modified silica gel; preconcentration; zinc